Visualization of peroxisomes via SKL-tagged DsRed protein in Sordaria macrospora - Skander Elleuche; Stefanie Pöggeler (Fungal Genetics Reports, 2008)
We report the utilization of Discosoma sp. red fluorescent protein DsRed to visualize peroxisomes in the filamentous ascomycete Sordaria macrospora. To achieve labeling of peroxisomes, DsRed was fused to a serine-lysine-leucine tag (SKL). Expression of theDsRed-SKL fusion gene under the control of the Aspergillus nidulans gpd-promoter led to protein import of DsRed into peroxisomes. In this study, we describe our results concerning the construction as well as the application of vector pDsRed-SKL.